FACTORS CONTRIBUTING TO LEARNING DIFFICULTIES AMONG GRADE IX STUDENTS AT SMP NEGERI 1 TOMA - Telaumbanua, Tatema; Kaminudin Telaumbanua; Baziduhu Laia; Murnihati Sarumaha; Fatolosa Hulu (Universitas Nias Raya, 2025)
This study aims to identify the factors influencing the learning difficulties of ninth-grade students at SMP Negeri 1 Toma in economics subjects. The problem addressed in this study is the factors that cause low learning outcomes in economics. The data collection methods used are questionnaires and documentation. Data analysis was conducted using the Product Moment correlation formula, the Spearman Brown formula, and the coefficient of determination (KD). This research analyzes two types of factors influencing students' learning difficulties: internal factors (physiological and psychological) and external factors (school environment and family environment). The results show that internal factors (physiological and psychological) have a correlation coefficient of r = 0.68, indicating a significant effect on students' learning difficulties. External factors, which involve the school and family environments, show a correlation coefficient of r = 0.86, indicating a very high influence on students' learning difficulties. The coefficient of determination (KD) for internal factors is 46.24%, while for external factors, it reaches 73.96%. Based on these findings, it is recommended that parents seek learning resources to motivate their children and provide constructive guidance to encourage more diligent studying.